The relationship of sex and aortic diameter at the time of acute type A aortic dissectionCentral MessagePerspective - Lamia Harik, MD; Mario Gaudino, MD, PhD; Mohammed Rahouma, MD; Arnaldo Dimagli, MD; Roberto Perezgrovas-Olaria, MD; Kevin R. An, MD; Talal Alzghari, MD; Giovanni Soletti, Jr., MD; Jordan Leith, BS; Gianmarco Cancelli, MD; Charles Mack, MD; Leonard N. Girardi, MD; et al. (JTCVS Open)
Objective: Evaluate sex differences in patients undergoing repair of acute type A aortic dissection (ATAAD). Methods: Sex-stratified, single-center cohort study of patients undergoing ATAAD repair from 1997 to 2022. The primary outcome was aortic diameter at time of presentation with ATAAD. Secondary outcomes were mortality, myocardial infraction, stroke, hemodialysis, tracheostomy, re-exploration for bleeding, a composite of major adverse events, and long-term survival. Results: In 390 consecutive patients (150 women), men were younger than women (61.0 years; interquartile range [IQR], 50-70 years vs 70.5 years; IQR, 59-78 years; P < .001), had higher body mass index (28.6; IQR, 25.1-32.3 vs 25.4; IQR, 21.9-29.2; P < .001), more frequent peripheral vascular disease (11.7% vs 4.7%; P = .03), renal insufficiency (36.7% vs 22%; P = .003), malperfusion (34.2% vs 18.7%; P = .007), and smoking history (65% vs 44%; P < .001). There was no sex difference in median aortic diameter at the time of ATAAD (men: 5.3 cm; IQR, 4.9-6.1 cm and women: 5.2 cm; IQR, 4.6-5.9 cm; P = .12) even when adjusted for body mass index (men: 5.7 cm; IQR, 5.4-6.1 cm and women: 5.4 cm; IQR, 5.4-6.1 cm; P = .19). There was no sex difference in mortality (4.6% vs 6.0%; P = .70), major adverse events, or 10-year survival (50.3% vs 58.5%; P = .13). On multivariable analysis, there was no interaction between aneurysm size and sex (interaction P = .62). Sex was not associated with major adverse events (odds ratio, 0.75; 95% CI, 0.07-7.39; P = .81). Conclusions: There was no sex difference in aneurysm size at the time of presentation of ATAAD, even after adjustment for body mass index, and no interaction between aneurysm size and sex, suggesting that aortic diameter remains a reasonable criterion for intervention irrespective of sex.